Bilingual online formative feedback in the development of critical thinking in native university students - Huamán-De-La-Cruz, Alejandro Máximo (2022)
Professional training in the university environment requires an adequate pedagogical treatment of bilingual online training feedback; which affects the significant development of critical thinking in students; For this reason, the following general objective has been formulated: to explain the influence of bilingual online formative feedback on the development of critical thinking in native university students. The research approach was quantitative, basic type, non-experimental design - transversal (causal correlational); the study sample was composed of 30 bilingual university students, chosen probabilistically. The questionnaire was applied via google meet for the collection of information. The results show that 66.7% of the students sometimes received bilingual online formative feedback from the teacher who teaches them; being so, sometimes, 56.7% of the students have received descriptive feedback; 63.3% discovery or reflective feedback and 50.0% evaluative feedback; As a consequence, 63.3% of students have developed high-level critical thinking skills. Whereas, it was concluded that: There is a statistically significant, moderate and directly proportional linear relationship between bilingual online formative feedback and the development of critical thinking in university students. ( = 0.558, p = 0,001 < 0.05).